Persepsi guru terhadap pemanfaatan tablet untuk tujuan pendidikan di Tanzania - James Leonard Mwakapemba; Edward Phabiano; Heri Retnawati (Jurnal Penelitian Pendidikan IPA, 2024)
The primary purpose of this study is to explore teachers' perceptions on the use of tablets for educational purposes in Tanzania for primary and secondary schools’ level of education. It aimed to identify three key variables, which are knowledge and skills on use tablets; school’s environmental support and sustainability of using tablets; and the attitudes of teachers towards using tablets. This study employed quantitative research approach by adopting post-positivist paradigm using research survey with Likert scale questionnaires through online. The study used the Technological Acceptance Model (TAM) to investigate the teachers’ attitudes towards using tablets for teaching and learning process. 81 respondents were involved in the study, samples were selected from five zones (North, South, West, East and Central zone). The data were analysed quantitatively using Winsteps version 5.7.0 through Rasch Model. Results found that (-0.18) of teachers had high knowledge and skills in the use of tablets, (-0.032) teachers agreed that the environment supports internet, electricity and accessibility of internet bundle on the use of tablets, and (-1.09) there was a strongly agreed for the acceptance of the use of tablets while (+0.47) teachers disagreed for the acceptance of the use of tablets for educational purposes in Tanzania.